Phosphatidylserine on blood cells and endothelial cells contributes to the hypercoagulable state in cirrhosis. (22nd June 2016) - Wu, Xiaoming; Yao, Zhipeng; Zhao, Lu; Zhang, Yan; Cao, Muhua; Li, Tao; Ding, Wenbo; Liu, Yan; Deng, Ruijuan; Dong, Zengxiang; Chen, He; Novakovic, Valerie A.; et al.
Abstract: Background & Aims: The mechanism of thrombogenicity in cirrhosis is largely unknown. Our objective was to study the relationship between phosphatidylserine on blood cells and endothelial cells and the hypercoagulable state in cirrhotic patients. Methods: Patients with cirrhosis and healthy controls were studied. Lactadherin was used to quantify phosphatidylserine exposure on blood cells and endothelial cells. Procoagulant activity of cells was evaluated using clotting time and purified coagulation complex assays. Fibrin production was determined by turbidity. Phosphatidylserine exposure, fibrin strands and FVa/Xa binding on cells were observed using confocal microscopy. Results: Our study showed that phosphatidylserine exposure on erythrocytes, platelets and leucocytes in cirrhotic patients increased progressively with Child–Pugh categories. In addition, we found that endothelial cells treated with cirrhotic serum in vitro exposed more phosphatidylserine than those exposed to healthy serum. The exposed phosphatidylserine supported a shorter coagulation time and increased FXa, thrombin and fibrin formation. Notably, phosphatidylserine + erythrocytes also promoted shorter coagulation times and more fibrin generation in cirrhotic microparticle‐depleted plasma, regardless of Child–Pugh categories. Confocal microscopy data showed that the FVa/FXa complex and fibrin fibrils colocalized with phosphatidylserine on endothelial cells. Lactadherin significantly inhibited FXa and thrombin generation and consequently decreased fibrin production in normal or cirrhotic plasma. Conclusions: These results lead us to believe that exposed phosphatidylserine on activated or injured erythrocytes, platelets, leucocytes and endothelial cells plays an important role in the hypercoagulable state in cirrhotic patients. Thus, blocking phosphatidylserine binding sites might be a new therapeutic target for preventing thrombosis.